Web ying yong cheng xu an quan = Web application security / = Web application security - Hoffman, Andrew (Zhongguo dian li chu ban she = China Electric Power Press Ltd., 2021)
Detailed summary in vernacular field.
880-04;O'Reilly Media, Inc. shou quan chu ban
Keywords: Computer networks -- Security measures; World Wide Web -- Security measures; Application software; Réseaux d'ordinateurs; Sécurité; Mesures; Web; Sécurité; Mesures; Logiciels d'application